Ethical challenges present in genomic research and biotechnology. Twenty years of Acta Bioethica - Rodríguez Yunta, Eduardo (Acta Bioethica, 2020)
This article reviews ethical reflections about genetic research and genetic manipulation published in 20 years of Acta Bioethica. The following relevant topics are identified in bioethics dialogue: risks evaluation, inequity, loss of biodiversity, eugenics, definition of limits between artificial and natural, dialogue between detractors and promoters of biotechnology, challenges in health care, information and confidentiality management. Reflections consider that bioethics can act as mediator among diverse stakeholders affronting the problems that arise when applying technology to life, allowing to recognize and to reach consensus for solving differences in equity, autonomy and the balance of risks and benefices. The reflections in Acta Bioethica are similar to those of other journals, but with emphasis in the Latin American region. In twenty years of reflection, the challenges are similar, but the emphasis is changing from preventing to the avoidance of actual risks of genetic modifications, which demands regulation of genetic engineering, taking into account that it is more effective than before. Among the benefits, genomic medicine has always generated more expectations than actual therapy with problems in demonstrating efficacy in clinical trials. With the new technique of genomic edition, there are even more expectations for enhancing therapeutic approaches, but worries increase about using genetic modifications without therapeutic aim and interventions that affect the social and ecological equilibrium.